2003
DOI: 10.1007/s00285-002-0190-6
|View full text |Cite
|
Sign up to set email alerts
|

Early development and quorum sensing in bacterial biofilms

Abstract: We develop mathematical models to examine the formation, growth and quorum sensing activity of bacterial biofilms. The growth aspects of the model are based on the assumption of a continuum of bacterial cells whose growth generates movement, within the developing biofilm, described by a velocity field. A model proposed in Ward et al. (2001) to describe quorum sensing, a process by which bacteria monitor their own population density by the use of quorum sensing molecules (QSMs), is coupled with the growth model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 30 publications
2
77
0
Order By: Relevance
“…Similarly, results of earlier research revealed that vibrios, including V. cholerae, attached to and used the chitinaceous exoskeleton and eggs of aquatic invertebrates as nutrient substrates (6,19,20,35,38,42,51). Thus, the ability to attach to live copepods in "hot spots," in microcolonies or biofilms, may be crucial for efficient nutrient capture and may be an important factor in the persistence and/or ascendance of one genotype over another (50).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, results of earlier research revealed that vibrios, including V. cholerae, attached to and used the chitinaceous exoskeleton and eggs of aquatic invertebrates as nutrient substrates (6,19,20,35,38,42,51). Thus, the ability to attach to live copepods in "hot spots," in microcolonies or biofilms, may be crucial for efficient nutrient capture and may be an important factor in the persistence and/or ascendance of one genotype over another (50).…”
Section: Discussionmentioning
confidence: 99%
“…They also explored therapy implications by incorporating a putative drug that targets bacteria expressing a particular gene during virulence (given that their models predict that only a fraction of the population will be up-regulated if one of the suppression mechanisms is operating). Finally, they extended Ward et al (2003) to include QS repressions in biofilm development and studied how it affects travelling wave behaviour.…”
Section: Qs Self-controlling Mechanismsmentioning
confidence: 99%
“…Pseudomonas aeruginosa Chopp et al (2002a, b), Ward et al (2003) Competence Streptococcus pneumoniae Karlsson et al (2007) C S P Exopolysaccharides - Frederick et al (2011) Motility (e.g. swimming, foraging) Tang et al (2007), van Gestel et al (2012) Virulence Pseudomonas aeruginosa Dockery and Keener (2001), Fagerlind et al (2003Fagerlind et al ( , 2005, Viretta and Fussenegger (2004), Netotea et al (2009) AHL, AHQ Koerber et al (2005), Jabbari et al (2010), Gustafsson et al (2004) AIP Escherichia coli Li et al (2006) AI-2, Indole Lee et al (2007) See Taga and Bassler (2003), Miller and Bassler (2001) and West et al (2012) for a more comprehensive list.…”
Section: Hunter Et Al (2013) Ahlmentioning
confidence: 99%
See 1 more Smart Citation
“…The ordinary differential equation-based spatiotemporal model discussed the correlations between the physical parameters and autoinducers in the biofilms matrix, where the biofilms were categorized into biotic part, consisting of living cells and abiotic materials, including EPS and dead cells. Then, Ward et al [62] considered the cell growth during the interaction between QS and biofilm formation. This model was based on a previous work, which described the QS system by three components: switch-off cells, switch-on cells and the switch, autoinducers, and assumed that higher concentrations of autoinducers increased the proportion of switch-on cells [63].…”
Section: Quorum Sensing (Qs)mentioning
confidence: 99%